ヒガシ ナンキョク プリンスオラフ カイガン デ オコナワレタ バクハ ジシン ジッケン ニ オケル コウコウ エイセイ ノ リヨウ 2. イチ ケッテイ - 渋谷, 和雄; シブヤ, カズオ; 伊藤, 潔; イトウ, キヨシ; 神沼, 克伊; カミヌマ, カツタダ; Shibuya, Kazuo; Ito, Kiyoshi; Kaminuma, Katsutada (1982)
P(論文) 1波(400 MHz)および2波(150 MHz, 400 MHz)のNNSS受信器による受信テストを昭和基地の天測点で行った。1波受信器による2次元的な(高さを固定した)衛星測位は, 多数の衛星軌道を用いて求められる平均位置から200mの標準偏差でばらつく。また, 2波受信器による2次元的な(高さを固定した)衛星測位は, 多数の衛星軌道を用いて求められる平均位置から緯度方向に25m, 経度方向に50mの標準偏差でばらつくことがわかった。上記の両者の平均位置は相対的に70-80m以内である。いくつかの衛星軌道のドップラーデータを加算し3次元的な衛星測位が求められるが, 軌道数に対する収束の見積もりを求めた。軌道数が3から7,15,25とふえていくと衛星測位の平面的な誤差は60m, 40m, 20m, 10mと減っていき, アンテナ高の誤差も20m, 10m, 10m, 5mのように減っていく。解析の結果によると, 天測測位とWGS-72標準楕円体上の衛星測位には約370-400mのずれが見られ, またアンテナ高度と海抜高度にも30±2mの差がある。第21次南極地域観測隊による爆破地震実験では, 27点の地震観測点の3次元的な衛星測位を15日間で行い, 各点についてそれぞれ3から25の衛星軌道を受信して, 実験の許容誤差以内で全点の位置決めを行うことができた。また, これらの観測点においてもアンテナ高度と海抜高度に20-40mの差が残った。上記高度差は近似的にジオイド高を与えるが, 求められた値は, SEASAT衛星の電波高度計解析から求められたジオイド図が示すこの地域の隣接海域の値と矛盾しない。10m以上の精度で衛星測位を行うためには, より多くの予報軌道を重ね合わせたり確定軌道を用いてもっと詳しい解析を行う必要がある。 Performance tests of a one-wave (400MHz) NNSS receiver and a two-wave (150 MHz and 400 MHz) NNSS receiver were made at Syowa Station, East Antarctica. The two-dimensional positioning by a one-wave receiver scattered with the standard deviation of about 200m from the mean position determined by many passes. The two-dimensional positioning by the two-wave receiver scattered with the standard deviation of 25m for the latitudinal direction and 50m for the longitudinal direction, respectively. The mean position by many passes by the one-wave receiver and that by the two-wave receiver were relatively located within 70-80m. Three-dimensional positioning was made by accumulating doppler data of several passes and the estimate of convergence was made by taking the number of satellite passes as a parameter. Probable error in two-dimensional co-ordinates was shown to reduce from 60m to 40m, 20m and further to 10m according as the pass number was increased from 3 to 7,15 and further to 25. The corresponding height error reduced from 20m to 10m and further to 5m according as the pass number was increased from 3 to 7-15 and further to 25. There is a difference of about 370-400m between the positioning by the satellite fixing on the WGS-72 earth ellipsoid ...